ХАЛҚ ДОСТОНЛАРИДА ҚАВМ-ҚАРИНДОШЛИККА ОИД ЛЕКСЕМАЛАР - Нарматова, М. (SCIENCE and SOCIETY, 2022)
This article talks about the place, meanings, etymology and levels of use of folk-kinship lexemes in historical and domestic life.